ANALYSIS OF MODERN OPTIMAL TREATMENT OPTIONS FOR PHARMACORESISTANT EPILEPSY - Yodgorov Jasurbek Jo’rayevich (World Scientific Research Journal, 2025)
Annotation This article analyzes the problem of pharmacoresistant epilepsy (PRE), its causes, and modern treatment methods. Advanced techniques used in global practice, such as neurosurgery, neurostimulation, and gene therapy, are examined. The aim is to identify the most effective and safe treatment approaches for patients who do not respond to pharmacotherapy.